Distribution and morphological measurements of wild and urban rodents from four habitats in the states of Selangor and Negeri Sembilan, Malaysia - M. Sithambaram, Paramasvaran; Abdullah Sani, Rehana; Krishnasamy, M.; Mustafa, Amal Nasir; Hassan, Latiffah; Mohd Zain, Siti Nursheena; Ibrahim, Latifah; Mat Sapran, Rahmat; Jeffery, John; Louis Masalamany, A. S. Santhana Raj; Sengol, Selvanesan (Department of Veterinary Services Malaysia, 2013)
A total of 204 rodents comprising of 14 species were identified from four different habitats namely urban, forest, paddy field and coastal. The Gombak forest reserve habitat was found to be ideal for the survival of 11 different rodent species. Maxomys rajah, Leopoldamys sabanus and Sundamys muelleri were the predominant rodent species distributed in the Gombak forest. Rattus ratus diardii was found mainly in the urban, paddy field and coastal habitat (67.1%). Morphological measurements of the rodents trapped from the four habitats did not show any major changes.